Detection of HMA5, PCs and MT2 Genes Expression in Vicia faba Under Heavy Metal Stress Using Quantitative Real-Time PCR - Khalid H. Alobaidi1 , Zaid N. Altememi2 , Dhafar N. Al-Ugaili3 , Jameel R. Al-Obaidi4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
In order to achieve phytoremediation during agricultural production, it is essential to identify high genotypesyield that is able of accumulating many types of heavy metals not in the edible parts which have significantnutritional value but in the non-edible parts. This study conducted to estimate the heavy metal ATPases 5(HMA5), Phytochelatins synthase (PCs) and metallothionein 2 (MT2) genes expression in plant Vicia fabain response to an elevated concentration of copper and zinc in nutrient media. Using Quantitative RealTime PCR (RT-qPCR) technique, the results of hydroponic culture methods with high concentrations ofcopper (75 µMol / L) and high concentration of zinc (500 µ Mol / L) showed high expression level for thethree genes of Vicia faba plant compared with control. Established that the expression of the genes underthe influence of copper ion was higher than the expression under zinc ion influence. Besides that, geneexpression increased with increased exposure time to zinc ion, also in the case of copper ion exposure time,all genes expression slightly increases with increased exposure time. In response to excess copper and zinc,an increase in the expression of genes (HMA5, PCs and MT2) involved in plant protection, providing thepossibility of its transfer from the cytosol to the apoplast demonstrate that this plant might be useful forphytoremediation of moderately polluted areas with copper or zinc.